Validation of apolipoprotein A-1 and fibronectin fragments as markers of parasitological cure for congenital chagas disease in children treated with benznidazole - Ruiz Lancheros, Elizabeth (2018)
Background. No reliable tests or validated biomarkers exist to ensure parasitological cure following treatment of Chagas disease (CD) patients chronically infected with Trypanosoma cruzi. As seroreversion, the only marker of cure, happens more quickly in children, we investigated the correlation between previously identified biomarkers and seroreversion in children. Methods. Thirty CD children (age 1 month to 10 years) diagnosed as T. cruzi positive (time point S0) were treated with benznidazole (BZ) 5-8 mg/kg/d for 60 days. At least 2 serological tests were used to evaluate treatment efficacy from the end of treatment (S1) until seroreversion (S2). Thirty children (age 1 month to 10 years) and 15 adults were used as healthy controls (HCs). Immunoblot and a proteomic-based assay were used to validate previously identified fragments of apolipoprotein A-1 (ApoA1) and fibronectin (FBN) as CD biomarkers. Results. Correlation between seroreversion and absence of ApoA1 and FBN fragments by immunoblot was observed in 30/30 (100%) and 29/30 (96.6%) CD children, respectively. ApoA1 and FBN fragments were absent at the end of BZ treatment in 20/30 (66.6%) and 16/30 (53.3%) children, respectively. Absence of fragments in serum profiles was confirmed by mass spectrometry. Using intact protein analysis, a 28 109-Da protein identified as full-length ApoA1 by tandem mass spectrometry was detected in HC serum samples. Conclusions. These data confirm that ApoA1 and FBN fragments can discriminate between healthy and T. cruzi-infected samples. Correlation with seroreversion was shown for the first time; results suggest predictive capacity potentially superior to serology, making them potentially useful as surrogate biomarkers.